PENDAMPINGAN MATERI DINIYAH BERBASIS ACTIVE LEARNING DI TPQ AL-HIDAYAH JELOK - Nur Muhammad Hakim; Muhammad Juliansyah Kurniawan; Ammar Bachweres; Maryono; Zaki Ulean Nuha (LPPM STAI Muhammadiyah Probolinggo, 2026)
This community engagement program aims to improve the quality of diniyah learning at TPQ Al-Hidayah Jelok through the implementation of active learning within the Asset-Based Community Development (ABCD) framework. The program was conducted over four weeks involving santri, teachers, and TPQ administrators. The ABCD approach was applied through stages of asset identification, program design, implementation, and evaluation. Data were collected through participatory observation, interviews, documentation, and descriptive learning evaluations. The findings indicate that active learning strategies such as small group discussions, structured question-and-answer sessions, simulations of worship practices, and simple presentations significantly enhanced students’ conceptual understanding and engagement. Santri were able to explain the pillars of faith and Islam in simple language, understand basic meanings of daily prayers, and perform ablution and prayer more systematically. In addition, students showed increased confidence, participation, and learning motivation. The program also strengthened teachers’ capacity to apply interactive learning methods independently. Overall, the integration of active learning within the ABCD framework effectively improved diniyah instruction quality and fostered sustainable collaborative learning practices at TPQ.